RECURRENT TEMPOROMANDIBULAR JOINT ANKYLOSIS AMONG YEMENIS: A PROSPECTIVE STUDY - Da'er, Sam Abd Alkarem; Farhan, Abdullah Hassan; Nasher, AkramThabet; Alareqi, Naif Rasheed; Juain, Ali Abdulwahed (Universal Journal of Pharmaceutical Research, 2023)
Background and aims: Recurrence of ankylosis is one of the most common complication following surgery especially during gap arthroplasty without interposition material. The main aim of these current study was to obtain a comparison between three different methods in prevent of recurrent temporomandibular joint ankylosis. Methods: A number of 15 patients with (2-22 years) age ranged between were obtained from those attending to Al-kawait Hospital, clinic of Oral and Maxillofacial Surgery Department, Sana’a University, Yemen. All patients in the present study that have ankylosis in the temporomandibular joint (TMJ) were included in period time from March 2017 to April 2020. the temporomandibular joint ankylosis Diagnosis was obtained through history of a chief complain, medical history, clinical and radiographic examinations. All patients were divided into three groups based on the type of treatment. Results: No any signs of surgical site infection in or around the incision. In group I: three cases of recurrence ankylosis were happened, while one case was dislodging of cartilage from harvested rib in group II. However, in group III, there were no complications observed after the end period of follow-up. Conclusion: The most effective procedure to prevent recurrence of temporomandibular joint ankylosis was the temporalis fascia as interpositional material, also produce a good esthetic and function results. Peer Review History: Received: 8 December 2022; Revised: 11 January; Accepted: 27 February 2023; Available online: 15 March 2023 Academic Editor: Dr. Asia Selman Abdullah , Pharmacy institute, University of Basrah, Iraq, asia_abdullah65@yahoo.com Reviewers: Dr. Tamer Elhabibi, Suez Canal University, Egypt, tamer_hassan@pharm.suez.edu.eg Dr. Bilge Ahsen KARA, Ankara Gazi Mustafa Kemal Hospital, Turkey, ahsndkyc@gmail.com